2017
DOI: 10.2527/jas2017.1642
|View full text |Cite
|
Sign up to set email alerts
|

Veal calf health on the day of arrival at growers in Ohio

Abstract: Veal calves are at high risk for disease and mortality in early life. Calves face a number of stressors before arriving at the grower, including long transport times, which may contribute to poor health. Our objectives were to 1) estimate the prevalence of poor health outcomes in veal calves on arrival at growers in Ohio; 2) determine risk factors for health outcomes on arrival, including BW and auction site (spread across 5 states in the Northeastern United States); and 3) determine if health outcomes on arri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 29 publications
0
42
1
1
Order By: Relevance
“…As the level of dehydration was associated with mortality (Renaud et al, 2018), the former may be true. Long transport has been shown to cause dehydration in young calves (Mormede et al, 1982;Knowles et al, 1997) and as calves are not provided with water during transit, transportation may be responsible for the high prevalence of dehydration (Pempek et al, 2017). Some degree of dehydration can be alleviated by providing electrolytes during transit, but the benefits are minor and this strategy may not be practical to implement in a commercial setting (Knowles et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the level of dehydration was associated with mortality (Renaud et al, 2018), the former may be true. Long transport has been shown to cause dehydration in young calves (Mormede et al, 1982;Knowles et al, 1997) and as calves are not provided with water during transit, transportation may be responsible for the high prevalence of dehydration (Pempek et al, 2017). Some degree of dehydration can be alleviated by providing electrolytes during transit, but the benefits are minor and this strategy may not be practical to implement in a commercial setting (Knowles et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, provision of oral fluids before departure from the dairy farm of origin could be a practical strategy to consider, where the fluids could alleviate any dehydration present before departure and mitigate the losses of fluids that may occur during transit. As dehydration is a common finding in calves arriving at veal facilities (Wilson et al, 2000;Pempek et al, 2017), more research is necessary to identify reasons for its high prevalence and strategies to reduce its impact on mortality and growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Male neonatal calves used for veal are highly susceptible to disease in early life. Two recent studies in North America have found that approximately 13 to 14% of calves arrive at growing facilities with diarrhea and that 26 to 27% arrive with abnormal or inflamed navels (Pempek et al, 2017;Renaud et al, 2018). At growing facilities, calves are often housed in individual pens with hard, slatted floors, presenting challenges for calf comfort.…”
Section: Short Communicationmentioning
confidence: 99%
“…On the day of arrival (cohort 1; n = 45 calves) or the third day after arrival (cohorts 2 and 3; n = 40 calves/ cohort), every third calf was fitted with a 3-dimensional accelerometer (Hobo Pendant G data loggers; Onset Computer Corp., Bourne, MA) on 1 of their hind legs (n = 125 calves across all 3 cohorts) using a plastic leg band and 3M VetWrap (3M, Maplewood, MN). This sample size was determined using a power analysis that included estimations of health effects from dairy cows and calves (Borderas et al, 2008;Cyples et al, 2012;Fogsgaard et al, 2012) and disease prevalence at arrival from previous studies on veal calves (Pempek et al, 2017;Renaud et al, 2018). We estimated needing least 12 calves in each health category and a total of 92 calves enrolled in the study to obtain this sample size; we intentionally recruited an additional 33 calves to ensure that we would obtain an adequate sample size for each health category after losses due to early mortalities or mechanical errors from the accelerometers.…”
Section: Short Communication: the Effect Of Diarrhea And Navel Inflammentioning
confidence: 99%